1990
DOI: 10.1056/nejm199003223221204
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ondansetron (Gr 38032F) and the Role of Serotonin in Cisplatin-Induced Nausea and Vomiting

Abstract: We compared the efficacy and safety of ondansetron (GR 38032F), a selective antagonist of serotonin S3 receptors, with that of placebo in controlling the nausea and vomiting induced by cisplatin treatment in 28 patients with cancer. The patients received either three intravenous doses of ondansetron (0.15 mg per kilogram of body weight) or normal saline (placebo) at four-hour intervals, beginning 30 minutes before the administration of cisplatin. Nausea and vomiting were markedly diminished in the group given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
152
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(161 citation statements)
references
References 34 publications
8
152
0
1
Order By: Relevance
“…The patterns of emesis observed with ondansetron and metoclopramide were similar for the remainder of the 24 h period. The urinary excretion of 5-hydroxyindole acetic acid (5HIAA), a metabolite of 5-HT, also has been shown to increase in the 4-6 h period after cisplatin paralleling the onset of emesis (Cubeddu et al, 1990). These observations suggested that shorter treatment regimens of ondansetron may be as effective as the continuous infusion or multiple dose schedules employed in the initial comparative studies.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…The patterns of emesis observed with ondansetron and metoclopramide were similar for the remainder of the 24 h period. The urinary excretion of 5-hydroxyindole acetic acid (5HIAA), a metabolite of 5-HT, also has been shown to increase in the 4-6 h period after cisplatin paralleling the onset of emesis (Cubeddu et al, 1990). These observations suggested that shorter treatment regimens of ondansetron may be as effective as the continuous infusion or multiple dose schedules employed in the initial comparative studies.…”
mentioning
confidence: 73%
“…This emphasises that the period up to 12 h following the cisplatin infusion may be the critical period for acute anti-emetic control. During this period, elevations in urinary levels of 5-HIAA, a urinary metabolite of 5HT, have been observed (Cubeddu et al, 1990). The plasma levels afforded by the 8 mg single dose are probably adequate for antagonising 5HT-mediated emesis at 5HT3 receptors, providing protection in the majority of patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In randomised studies it has been proven superior to both placebo (Cubeddu et al, 1990) and high dose metoclopramide (Marty et al, 1990) in controlling cisplatin induced emesis. In non-cisplatin containing chemotherapy regimens it has been shown superior to metoclopramide in four randomised studies (Schmoll, 1989;Kaasa et al, 1990).…”
mentioning
confidence: 99%
“…Until recently, even with the use of the most active antiemetic combination regimen (metoclopramide with lorazepam and dexamethasone), a considerable proportion of patients suffered from nausea and vomiting whereas the new 5HT3-antagonists are now found to be more effective in preventing acute nausea and vomiting induced by cisplatin (Cubbedu et al, 1990;Marty et al, 1990;Smith et al, 1990; de Mulder et al, 1990). …”
mentioning
confidence: 99%